Systematic Review and Meta-analysis of Long-term survival After Elective Infrarenal Abdominal Aortic Aneurysm Repair 1969–2011: 5 Year Survival Remains Poor Despite Advances in Medical Care and Treatment Strategies. Issue 3 (September 2015) - Bahia, S.S.; Holt, P.J.E.; Jackson, D.; Patterson, B.O.; Hinchliffe, R.J.; Thompson, M.M.; Karthikesalingam, A.
Abstract : Background: Improved critical care, pre-operative optimization, and the advent of endovascular surgery (EVAR) have improved 30 day mortality for elective abdominal aortic aneurysm (AAA) repair. It remains unknown whether this has translated into improvements in long-term survival, particularly because these factors have also encouraged the treatment of older patients with greater comorbidity. The aim of this study was to quantify how 5 year survival after elective AAA repair has changed over time. Methods: A systematic review was performed identifying studies reporting 5 year survival after elective infrarenal AAA repair. An electronic search of the Embase and Medline databases was conducted to January 2014. Thirty-six studies, 60 study arms, and 107, 814 patients were identified. Meta-analyses were conducted to determine 5 year survival and to report whether 5 year survival changed over time. Results: Five-year survival was 69% (95% CI 67 to 71%, I 2  = 87%). Meta-regression on study midpoint showed no improvement in 5 year survival over the period 1969–2011 (log OR −0.001, 95% CI −0.014–0.012). Larger average aneurysm diameter was associated with poorer 5 year survival (adjusted log OR −0.058, 95% CI −0.095 to −0.021, I 2  = 85%). Older average patient age at surgery was associated with poorer 5 year survival (adjusted log OR −0.118, 95% CI −0.142 to −0.094, I 2  = 70%). After adjusting for average patient age, an improvement in 5 year survival over the period that these data spanned was obtained (adjusted log OR 0.027, 95% CI 0.012 to 0.042). Conclusion: Five-year survival remains poor after elective AAA repair despite advances in short-term outcomes and is associated with AAA diameter and patient age at the time of surgery. Age-adjusted survival appears to have improved; however, this cohort as a whole continues to have poor long-term survival. Research in this field should attempt to improve the life expectancy of patients with repaired AAA and to optimise patient selection.